Current account adjustment in EU countries: Does euro-area membership make a difference? - Sabine Herrmann; Axel Jochem (Deutsche Bundesbank, 2013)
The paper evaluates current account dynamics in countries with different exchange rate regimes within the EU. In this, the empirical analysis explicitly differentiates between countries with a flexible and a fixed exchange rate regime and members of a monetary union. In addition, we model the adjustment process of external disequilibria by referring to the flexibility of exchange rates and interest rates. The sample covers annual data for 27 EU countries from 1994 to 2011. The estimation is based on a simple autoregressive model and comes to the conclusion that current account adjustment is significantly hampered in countries that are members of a monetary union. This holds particularly in comparison with floating exchange rate regimes owing to lower exchange rate flexibility. However, the persistence of current account balances in member countries of a monetary union is also more pronounced than in fixed-rate regimes due to less flexible interest rates as a result of the single monetary policy.
Keywords: E52; F32; F33; F34; 330; Balance of Payments; European Monetary Union; Exchange Rate Regime; Current Account Adjustment; Financial Crisis